2018
DOI: 10.1108/he-04-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Drinking to the “edge”: gender differences in context-specific risks

Abstract: Purpose The risk associated with heavy episodic drinking in young people has caused concern among public health professionals. The purpose of this paper is to investigate the gender differences in the perception of risk in alcohol consumption behaviour for better targeting of messages. Design/methodology/approach This qualitative descriptive study examines the narratives of 28 young people’s experience of a “night out” framed as the Alcohol Consumption Journey to examine the ways young men and women experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In general, the community groups and venue managers perceived risk with high incidents of violence with physical and sexual threats to young people. This is consistent with the findings of previous studies (Waitt et al, 2011;Armstrong et al, 2014;Dresler and Anderson, 2018a). Regarding perceived risk, one of the main issues that arose was that venues (pubs, bars, nightclubs and restaurants) that catered to younger people were largely focussed on alcohol consumption.…”
Section: Activity Settingsupporting
confidence: 90%
See 2 more Smart Citations
“…In general, the community groups and venue managers perceived risk with high incidents of violence with physical and sexual threats to young people. This is consistent with the findings of previous studies (Waitt et al, 2011;Armstrong et al, 2014;Dresler and Anderson, 2018a). Regarding perceived risk, one of the main issues that arose was that venues (pubs, bars, nightclubs and restaurants) that catered to younger people were largely focussed on alcohol consumption.…”
Section: Activity Settingsupporting
confidence: 90%
“…It would be valuable to investigate broader social and structural contexts of the community level to provide insights on the potential influences of higher levels on the risk associated with excessive drinking in young people. Also, the findings of this study will add to the body of knowledge from the perspectives of lower levels of the social ecological model (Fry, 2011;Armstrong et al, 2014;Dresler and Anderson, 2017;Dresler and Anderson, 2018a). Especially, research on the lower levels is considered important as they highlight the critical disconnection between individuals and the situational factors that influence risky drinking practices in specific contexts.…”
Section: Policy/enabling Environmentmentioning
confidence: 82%
See 1 more Smart Citation
“…50 In contrast, research demonstrated that young New Zealand male participants (aged 18-24 years) adopted more individualistic strategies for managing alcohol-related risks than female participants of the same age, and they lacked awareness that safety can be associated with consuming alcohol in trusted groups. 51 Furthermore, both male and female participants in this New Zealand study showed reluctance towards helping an unknown intoxicated man in a risky situation-demonstrating the vulnerability of intoxicated men. 51 Among the safety strategies identified in the current study, men were more likely to discuss limiting the amount of alcohol they consumed than using a sober supervisor, with some referencing knowledge of their alcohol limits as guidance for this "Just keeping to your limit, I guess.…”
Section: How Do Young Adults Keep Themselves Safe In Aquatic Settings When Alcohol Is Involved?mentioning
confidence: 78%
“…Moreover, social standards impose different meanings of alcohol consumption for men and women, creating different patterns of drinking and risks while they are socialising ( de Visser, & McDonnell, 2012;Lindsay, 2006;Lyons & Willott, 2008). For example, although in male culture the excessive consumption of alcohol is accepted, women are expected to uphold a certain degree of control and respectability (Dresler & Anderson, 2018).…”
Section: Gender Violence and Intensive Alcohol Consumption In The Nigmentioning
confidence: 99%